Behavioral activation, inhibition and mood symptoms in early-onset bipolar disorder. - Biuckians, A; Miklowitz, D; Kim, E (2007)
BACKGROUND: Hypomania/mania and depression are hypothesized to correspond to high and low expressions of behavioral activation system (BAS) activity, respectively, in bipolar individuals. In contrast, behavioral inhibition system (BIS) activity is hypothesized to regulate anxiety. The aim of the present study was to examine whether self-reported levels of BAS functioning in bipolar adolescents corresponded with levels of concurrent manic and depressive symptomatology. The secondary aim was to investigate whether self-reported BIS levels were associated with self-reported anxiety symptoms. METHODS: Twenty-five adolescents diagnosed with bipolar I, II or not otherwise specified were recruited from a treatment-development study. Adolescents were interviewed using the Depression and Mania Rating Scales of the Kiddie Schedule for Affective Disorders and Schizophrenia and given the Self-Report for Childhood Anxiety Related Disorders. Next, they completed the Behavioral Inhibition/Activation Scales. RESULTS: Contrary to hypotheses, adolescents with higher BAS levels exhibited less severe concurrent mania symptoms. Furthermore, levels of BAS sensitivity were not associated with concurrent levels of depression. As predicted, BIS scores correlated positively with self-reported anxiety scores. Adolescents reporting higher levels of the motor activity symptoms of mania also reported higher levels of anxiety symptoms. LIMITATIONS: The conclusions are based upon cross-sectional analyses in a small sample. CONCLUSIONS: In bipolar adolescents, mania and depression appear to be independent of self-reported behavioral activation levels. However, mood symptoms in adolescent patients are closely tied to components of anxiety, which may lead to diminished approach behaviors.